What does Google Trends reveal about the proportion of waterpipe users in the Brazilian population? - Fernando Lopes Tavares de Lima; Luís Felipe Leite Martins; André Salem Szklo (Ministério da Saúde do Brasil, 2023)
ABSTRACT Objective To analyze the relationship between internet search volume and the prevalence of waterpipe use among young Brazilians in 2019. Methods This was a descriptive study with data from Brazil in 2019, using the relative search volume on waterpipes extracted from Google Trends and the proportion of waterpipe users aged between 15 and 24 years, as measured by the National Health Survey (Pesquisa Nacional de Saúde - PNS), and aged between 13 and 17 years, as measured by the National Adolescent School-based Health Survey (Pesquisa Nacional de Saúde do Escolar - PeNSE). The relationship was assessed by means of Spearman's correlation. Results The point prevalence of waterpipe use across the Brazilian Federative Units (FUs) showed a moderate (r = 0.51; PNS) to strong correlation (r = 0.74 and r = 0.80; PeNSE) with the relative search volume (p-value < 0.05). Conclusion Google Trends can support the monitoring system on waterpipe use in the FUs, providing additional information to existing population-based surveys.